Global Child Rights vs. Local Traditions: A Pentahelix Study of Child Marriage in Bone Regency - Hastira, Muhammad Fajhriyadi; Fadhilah, Nurul; Maksum, Ali; Khairullah, Septi (Jurnal Studi Pemerintahan, 2025)
This study discusses the dynamics of localizing global norms for child protec- tion in the context of preventing child marriage in Bone Regency through Amitav Acharya’s localization theory and the Pentahelix collaborative model. Although Indonesia has ratified the Convention on the Rights of the Child and imple- mented various national policies, the practice of child marriage remains preva- lent due to the strength of local social and cultural norms, such as the value of siri’ na pacce and literal interpretations of religious teachings. This study employs a qualitative approach with in-depth interviews of key actors, includ- ing local government officials, religious leaders, academics, children’s forums, and the media. The findings show that the SIP PEKA program has success- fully reduced the number of child marriage dispensations by integrating con- textual educational, regulatory, and participatory approaches. However, chal- lenges remain in the form of limited binding local regulations, limited media support, and sectoral egoism among agencies. Therefore, stronger cross- sectoral collaboration and broader community participation are key to strengthening the program’s sustainability. This research contributes to inter- national relations studies by highlighting how global norms can be absorbed and reinterpreted in local contexts through responsive and participatory ap- proaches.